ANALISIS KAUSALITAS KOMUNIKASI TIDAK EFEKTIF DALAM PROYEK KONSTRUKSI DENGAN PENDEKATAN PLS-SEM - Dwi Saputro, Meidra Yusuf (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
The analysis results indicate that the variables of material quality and construction work (X1) and project management and coordination (X2) have a significant impact on project effectiveness and satisfaction (Y), with path coefficients of 0.890 and 0.908, respectively. The R-Square value of 0.946 suggests that 94.6% of the variability in project effectiveness and satisfaction can be explained by these two variables. These findings highlight the importance of improving communication and coordination to achieve more effective and satisfying project outcomes.